Assessment of differential renal function in unilateral hydronephrosis by unit area formula against classic method in Tc-99m DMSA scintigraphy before and after intervention - Kepenek, F.; Koc, Z.; Orhan, I.; Balci, T.; Aydin, F.; Gungor, A. (Springer, 2013)
[Abstract Not Available]
Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- OCT 19-23, 2013 -- Lyon, FRANCE